Investigations on the effect of aspect ratio into the performance of savonius rotors - Roy, Sukanta; Saha, U. (2013)
With the rapid execution in the renewable energy field, vertical axis wind turbines are finding its application in the small-scale distributed wind energy generation, particularly in rural areas. The Savonius rotor is a drag based vertical axis wind turbine and is used as a small-scale wind energy converter with low installation and maintenance cost. These rotors are simple in design, easy to assemble and can be operated at lowspeed wind from any direction. However, these rotors are not gaining popularity because of its low efficiency and improper design. The aspect ratio (height to diameter of the rotor) is one of the very important factors for designing a suitable small-scale wind turbine. The other important factors include overlap ratio, gap ratio and blade profile of the rotor. In the present investigation, a number of rotor models with different aspect ratios are tested in a low speed wind tunnel with open test section facility. The effects of overlap ratio and gap ratio are also studied keeping the rotor height to be the same. The wind speed is varied from 5-10 m/s. To estimate the performance of these rotors, electrical loads are given with respect to different wind speeds and the power output is calculated in terms of voltage and current. The results depicted an optimum aspect ratio of 0.80, which can be used to improve the performance of Savonius rotors.